The Exploring Emotions Through Movement Exploration And Improvisation As Art Therapy In Dance Extracurricular At State Senior High School 21 Surabaya: Exploring Emotions Through Movement Exploration And Improvisation As Art Therapy In Dance Extracurricular At State Senior High School 21 Surabaya - Pratiwi, Nabila Budhi; Handayaningrum, Warih (Solah, 2026)
This study aims to analyze the implementation of dance learning in extracurricular activities at SMA Negeri 21 Surabaya, with a focus on the steps of exploration and improvisation of movement as a medium for pouring out students' emotions. Using a qualitative approach with a case study method, this study involved dance extracurricular participants as the main subjects. The results of the analysis show a strong impact between the emotions experienced and the displayed movement expressions, including aspects of body posture, direction and space of movement, tempo, quality, and symbolic meaning. Quantitative assessment scores on the aspects of openness, expression, coordination, and energy indicate excellent performance in integrating emotions into movement. This extracurricular activity proved to be a safe space for participants' emotional expression which was nurtured through stages of warm-up, exploration, improvisation, and evaluation. The conclusion of this study confirms that the exploratory and improvisational approach is effectively used as a form of art therapy that supports the emotional and psychological development of students.